Étude de l’activité antibactérienne de Taraxacum officinale - BOUSBA, Imene; HENNOUS, Fatima Zohra (My University, 2021)
The objective of this present work is to study the antimicrobial power of the extract from a plant of Taraxacum officinale collected in the region of Mostaganem on six microorganisms tested: Candida albicans ATCC 10231, Salmonella typhimurium ATCC 14028, Staphylococcus aureus ATCC 33862, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, Klebsiella pneumoniae ATCC 13883. The results are expressed by the diameter of the zones of inhibitions by the disk diffusion method and the determination of minimum inhibitory concentration (MIC). The test results revealed the following diameters in descending order, with Pseudomonas aeruginosa ATCC 27853 (15.66 ± 0.93mm), Klebsiella pneumoniae ATCC 13883 (13.5 ± 0.40mm), Candida albicans ATCC 10231 (12.66 ± 1.2mm), Salmonella typhimurium ATCC 14028 (7.33 ± 0.45mm), Staphylococcus aureus ATCC 33862 (7.33 ± 0.45mm) and Escherichia coli ATCC 25922 (11 ± 2.44mm). The highest minimum inhibitory concentration (MIC) was recorded with Klebsiella pneumoniae ATCC 13883 and which is of the order (50μg / ml), while the lowest MIC was noted with Salmonella typhimurium ATCC 14028 and Candida albicans ATCC 10231 (6, 25μg / ml). These results suggest the possibility of using Taraxacum officinale extract as a treatment for certain fungal infections and pathogenic bacteria.
Keywords: Taraxacum officinale - antimicrobial activity - pathogens - MIC.